A Non-Technical Introduction to Electropenetrography and its Application with Asian Citrus Psyllid as an Example - T. A. Ebert; A. W. Schumann; A. J. Krajewski (EDIS)
Protecting plants by targeting insect vectors of pathogenic organisms requires an intimate understanding of the biology of the insect, the pathogen, and the plant host at a spatial scale relevant to the insect. Observing insect feeding is difficult because insect mouthparts are small, and many insects insert their mouthparts deep inside plants, where we cannot see them. Electropenetrography (EPG) is the only technique that overcomes these problems. Using EPG, we can  understand host-insect relationships, pesticide action, and the role of non-hosts. EPG can address ecological questions like "how do insects survive long migrations over regions devoid of known host plants?" It can also address applied questions: "will the pest feed on my new cultivar?" This light introduction to an underused key technology focuses on the Asian citrus psyllid, but EPG has great potential to improve pest management efforts for several different crops and insect vectors.